2018
DOI: 10.4314/jasem.v22i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on Polycyclic Aromatic Hydrocarbons (PAHS) concentrations in catfish and tilapia muscles

Abstract: ABSTRACT:The effects of smoking on proximate composition, energy values and concentrations of polycyclic aromatic hydrocarbons (PAHs) were studied in raw and smoked samples of catfish (Clarias gariepinus) and tilapia (Oreochromis niloticus). Crude protein was higher in the tilapia sample for both raw and smoked samples. There was significant difference (P<0.05) in the lipid contents of raw and smoked samples of both species. Mean naphthalene concentration was significantly higher (P<0.05) than those of other P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
4
2
Order By: Relevance
“…Table 4 showed the comparison of the distribution of total mean PAHs in the smoked catfish of this present study with findings from related studies [15]. Similar observations detected high PAHs concentrations in catfish (69.645 μg/kg) and tilapia fish (42.115 μg/kg) respectively in which naphthalene showed the highest concentrations in both samples [15]. The result of this study also agrees with some other findings on the effect of cooking methods on food materials [16].…”
Section: Comparison Of the Pah Concentration In The Smoked Catfish With Similar Studiessupporting
confidence: 90%
See 2 more Smart Citations
“…Table 4 showed the comparison of the distribution of total mean PAHs in the smoked catfish of this present study with findings from related studies [15]. Similar observations detected high PAHs concentrations in catfish (69.645 μg/kg) and tilapia fish (42.115 μg/kg) respectively in which naphthalene showed the highest concentrations in both samples [15]. The result of this study also agrees with some other findings on the effect of cooking methods on food materials [16].…”
Section: Comparison Of the Pah Concentration In The Smoked Catfish With Similar Studiessupporting
confidence: 90%
“…The average total PAH level of smoked catfish (2.576 μg/kg) was lower than the findings of some researchers who also studied the effect of smoking on the accumulation of PAHs on catfish and tilapia fish and obtained mean concentrations of 69.645 μg/kg and tilapia fish 42.115 μg/kg for catfish and tilapia fish respectively [15]. The result of this work revealed that the accumulation of PAHs by the catfish samples is directly proportional to smoking duration showing increasing order of total PAHs concentrations.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Similar trend was observed for fresh and dried fish (M. undulantes) collected from Escravos Estuaries ranging from 0.0014 to 0.073 mg/kg and 0.025 to 0.129 mg/kg. Results obtained from dried and fresh sample were not as high as those reported by Nnaji and Ekwe (2018) those from Escravos Estuaries ranged from 0.003 to 0.0029 and 0.00 to 0.029 mg/kg for fresh fish as well as 0.001 to 0.012 and 0.001 to 0.029 mg/kg for dried fish (M. undulantes). This value is far more than that reported by Pierre et al 2012 Figure 1 shows a gas chromatogram of PAHs' profile of oil extracted from fresh catfish harvested from pond (Pond FF2) with total PAHs concentration of 0.019 mg/kg which is in the range of 0.035 to 0.069 mg/kg as stated earlier in Table 1.…”
Section: Resultscontrasting
confidence: 57%
“…In consistence with other studies across the world, PAHs manifestation was confirmed in arrays of consumables across Africa such as; smoked Bush meats in Kumasi, Ghana and was revealed to have contained PAHs below the EU peg limits for smoked meats, this is according to Abu, (2013). In a related work the 16 priority PAHs were detected in smoked Tilapia Fish and Catfish, revealed through a research conducted by Nnaji & Ekwe, (2018). They were equally, report in smoked cephalopods, crustaceans, bivalve molluscs, and baby foods (Ijeoma et al, 2015a).…”
Section: Occurrence Of Pahs In Foodmentioning
confidence: 97%